Evaluation Setup Process on Rotogravure Printing Machine in Oder to Reduce Setup Time - Wirakusuma, Kadex Widhy; Singgih, Moses Laksono (IPTEK Journal of Proceedings Series, 2019)
The company carries out various ways to be able to meet customer demand quickly, one of which is to speed up the production process. In the printing process, the company encountered a problem, one of which was the high downtime caused by the setup process. The standard setup time determined by the company is 150 minutes but in fact the time required is 211.33 minutes. This shows that there are inefficient methods applied by the company. In this study, we will evaluate the work method to get errors so that the setup duration becomes high. This study will draw on the Modified Cooper Harper Scale and Single Minute Exchange of Dies (MCH-SMED) method to balance the workload between operators so that the setup time can be reduced. The MCH method is used to analyze the mental and physical workload on an operator based on a tree decision scale so that it can balance the workload between operators. SMED is used to identify on-line and off-line operations in the setup process. This study aims to produce a comparison of the standard setup times that have been set by the company and after evaluating the integration process of printing machine setup (MCH-SMED). The results of this study are to obtain a new sequence of operations that can reduce the duration of setup time to 143.19 minutes or be able to reduce the setup time by 32%